2009
DOI: 10.3201/eid1505.081119
|View full text |Cite
|
Sign up to set email alerts
|

A Case–Control Study on the Origin of Atypical Scrapie in Sheep, France

Abstract: A matched case-control study (95 cases and 220 controls) was designed to study risk factors for atypical scrapie in sheep in France. We analyzed contacts with animals from other fl ocks, lambing and feeding practices, and exposure to toxic substances. Data on the prnp genotype were collected for some case and control animals and included in a complementary analysis. Sheep dairy farms had a higher risk for scrapie (odds ratio [OR] 15.1, 95% confi dence interval [CI] 3.3-69.7). Lower risk was associated with org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 33 publications
(48 reference statements)
1
41
0
Order By: Relevance
“…Recent studies revealed that polymorphisms of codons 141 and 154 are correlated with atypical scrapie development (12,22); moreover, in a matched case-control study, atypical scrapie related genotypes were classified into five risk groups (group 1 to group 5) according to their odds ratio (13). Classification of the Karacabey …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that polymorphisms of codons 141 and 154 are correlated with atypical scrapie development (12,22); moreover, in a matched case-control study, atypical scrapie related genotypes were classified into five risk groups (group 1 to group 5) according to their odds ratio (13). Classification of the Karacabey …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, counties with a large percentage of small flocks (<20 ewes) might have been overrepresented. To assess the influence of geographic selection bias, we conducted a sensitivity analysis by using 2 methods: (1) weighting of controls in the final model with weights being defined for each county as the ratio of the percentage of flocks >20 ewes in the county divided by the percentage of flocks >20 ewes at the national scale, and (2) introduction of sheep production areas as random coefficients in the final model.78 …”
Section: (E) Describe Any Analyses Used To Assess the Robustness Ofmentioning
confidence: 99%
“…The analysis of the data collected through the active surveillance program (Fediaevsky et al, 2010;Fediaevsky et al, 2009) seems to indicate that the capacity of Atypical scrapie cases to transmit disease to other sheep under field conditions is low and possibly nil. In most of the Atypical scrapie flocks, only a single case is found.…”
Section: Atypical Scrapiementioning
confidence: 99%
“…At slaughterhouse the main biases include over or under representation of some geographical regions, non random timing of sampling such as systematic same week days for sampling, sampling rate related to flock size or commercial pattern, biases on animal age or general appearance (Del Rio Fediaevsky et al, 2009;Tongue et al, 2008).…”
Section: Tse Epidemiological Situation In the Small Ruminant Europeanmentioning
confidence: 99%